Identification and management of Lynch syndrome in the Middle East and North African countries: outcome of a survey in 12 countries - Sina, Mohammad; Ghorbanoghli, Zeinab; Abedrabbo, Amal; Al-Mulla, Fahd; Sghaier, Rihab Ben; Buisine, Marie-Pierre; Cortas, George; Goshayeshi, Ladan; Hadjisavvas, Andreas; Hammoudeh, Wail; Hamoudi, Waseem; Jabari, Carol; et al. (Familial cancer, 2021)
Lynch syndrome (LS), the most common inherited form of colorectal cancer (CRC), is responsible for 3% of all cases of CRC. LS is caused by a mismatch repair gene defect and is characterized by a high risk for CRC, endometrial cancer and several other cancers. Identification of LS is of utmost importance because colonoscopic surveillance substantially improves a patient’s prognosis. Recently, a network of physicians in Middle Eastern and North African (ME/NA) countries was established to improve the identification and management of LS families. The aim of the present survey was to evaluate current healthcare for families with LS in this region.